The Privatisation of a National Project: The settlements along the Trans-Israel Highway since 1977 - Schwake, Gabriel (A+BE | Architecture and the Built Environment, 2020)
In Israel, the development of new settlements is a leading national project. This began in the turn of the 20th century as national Zionist organisations established new frontier settlements in Palestine, in the efforts to secure the territory needed for a future state and to encourage a spiritual national renaissance. With its establishment in 1948, the young state of Israel took over the process, continuing the pre-state settlement endeavours of securing spatial control while endorsing a new unified national identity. Accordingly, the state promoted, directed, and executed the construction of a series of rural and industrial settlements that corresponded with the national geopolitical agenda and the hegemonic socialisation policy. Consequently, the architectural and urban features of these settlements were parallel to the ruling political, economic and social values and were thus characterised by reproduced homogeneous and economical residential environments. During the 1970s, the monolithic state-led development began to transform with the growing privatisation of the Israeli economy. These transformations reached a point of no return with the election of the first liberal and anti-socialist government in 1977; eventually turning into a national consensus. At the same time, the state did not abandon its geopolitical agenda and the attempts of securing spatial control through settlement. Nevertheless, it began dismantling its monopoly over the establishment of new localities, granting selected group spatial privileges and thus turning them into spatial agents that develop the frontier on its behalf. Initially, the privatisation of the national settlement project began with ex-urban and suburban communities, serving favoured societal groups. Eventually, with the growing involvement of private capital, it turned into a large-scale corporate-led development venture, dictated by financial interests while fulfilling geopolitical objectives. Privatisation, neoliberalism and market-economy are usually used as an antithesis to state involvement, regulation and nationalism. Conversely, this dissertation illustrates that the privatisation of the national territorial project was a statedirected effort intended to align the geopolitical agenda with the prevailing neoliberal order; using the market-economy as a means to enhance the state’s control over space. This dissertation focuses on the border area with the occupied Palestinian West-Bank, the Green-Line. Scarcely populated in the first three decades after the establishment of Israel, this area witnessed an ever-growing state-directed development effort following the occupation of the Palestinian territories in 1967. Developed by an increasing private involvement, this area constitutes a unique case study on the relationship between geopolitics and market economy; marked by the construction of the first privately developed national infrastructure project in the early 2000s – the Trans-Israel Highway. To understand the privatisation of this national project since 1977, this dissertation proposes focusing on the settlement mechanism. This comprises the reciprocal interests of the state and various private groups to develop and domesticate the frontier area of the Green-Line. Centring on the spatial privileges the state granted diverse spatial agents, this dissertation examines how different favoured groups were given the power to colonise, plan, develop and market space in return for enhancing the state’s power over it. Investigating how this settlement mechanism transformed over the years, including a variety of spatial agents and diverse spatial privileges, this research explores the increasing privatisation of the local economy and culture, as well as the manner in which it was manifested in the built environment. Examining the modifications in the architectural and urban products this mechanism produced, this research analyses the materialisation of the privatised national settlement project and how it transformed together with the changing political and economic interests. Focusing on the area along the Green-Line, this dissertation starts with examining the Community Settlements of the late 1970s and then moves to the Suburban Settlements of the 1980s. Examining both phenomena, the dissertation explains how their ex-urban and suburban qualities corresponded with the granted spatial privileges, forming a geopolitical tool intended to domesticate the Green-Line. Subsequently, the dissertation concentrates on the mass suburbanisation of the 1990s and the financialisation of the 2000s. Examining both stages, this dissertation illustrates how the state asked to domesticate the frontier by turning it into a real estate market; directing investment while securing the developers’ profitability and rentability concerns. Observing these four stages, this dissertation examines the gradual privatisation of the settlement mechanism. Analysing the different settlement phenomena, this research explains how the transforming individual and corporate interests were manifested in the built environment. Eventually, enabling the continuation of the national geopolitical agenda by tying it to the rationale of the market; replacing the former monolithic state-led development by uniform and reproduced corporate-led projects.